Event-Triggered Output Feedback Control for a Class of Nonlinear Systems via Disturbance Observer and Adaptive Dynamic Programming - Yang, Yang; Fan, Xin; Gao, Weinan; Yue, Wenbin; Liu, Aaron; Geng, Shuocong; Wu, Jinran (IEEE transactions on fuzzy systems, 2023)
An event-triggered output feedback control approach is proposed via a disturbance observer and adaptive dynamic programming (ADP). The solution starts from constructing a nonlinear disturbance observer which only depends on the measurement of system output. A state observer is then developed based on approximation information of system dynamics via neural networks. In order to avoid continuous transmission and reduce communication burden in the closed-loop system, an event-triggered mechanism is introduced such that the control signal is updated only at specific instant that a triggered condition is violated. By virtue of the disturbance observer and state observer, an output-feedback ADP control approach then is developed, where only a critic network is employed to estimate the value function. Based on Lyapunov stability theory, stability of the closed-loop system is rigorously analyzed, and the effectiveness of the proposed control approach is verified by two simulation examples.